2020
DOI: 10.21203/rs.3.rs-38253/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consequences of the COVID-19 pandemic on the continuum of the care in a cohort of people living with HIV followed in a single center of Northern Italy

Abstract: Introduction: During the COVID-19 pandemic, hospitals faced increasing pressure, where people living with HIV risked to either acquire SARS-CoV-2 and to interrupt the HIV continuum of care.Methods: this is a retrospective, observational study. We compared the numbers of medical visits performed, antiretroviral drugs dispensed and the number of new HIV diagnosis and of hospitalizations in a cohort of people living with HIV (PLWH) followed by the Spedali Civili of Brescia between the bimester of the COVID-19 pan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Finally, in line with the findings of another Italian study, we observed a decline in the number of determination-naive PLWH; however, this trend existed before the pandemic, which may therefore not have been a causal factor. 8 On the other hand, a large study investigating the impact of lockdown on HIV care in South Africa found that there was a 47.6% reduction in HIV testing in April 2020, and a significant reduction in the number of patients starting ART although, like us, the authors did not find any significant change in the number of patients picking up their medications. 21 Given the greater consideration that needs to be given to strategies aimed at facilitating HIV testing and promptly starting ART during the pandemic, it is interesting to note that an American study has highlighted the importance of implementing HIV self-testing.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Finally, in line with the findings of another Italian study, we observed a decline in the number of determination-naive PLWH; however, this trend existed before the pandemic, which may therefore not have been a causal factor. 8 On the other hand, a large study investigating the impact of lockdown on HIV care in South Africa found that there was a 47.6% reduction in HIV testing in April 2020, and a significant reduction in the number of patients starting ART although, like us, the authors did not find any significant change in the number of patients picking up their medications. 21 Given the greater consideration that needs to be given to strategies aimed at facilitating HIV testing and promptly starting ART during the pandemic, it is interesting to note that an American study has highlighted the importance of implementing HIV self-testing.…”
Section: Discussionmentioning
confidence: 56%
“…6,7 The provision of HIV services was particularly challenging in countries such as Italy, where the delivery of HIV care and ART is almost exclusively ensured by specialists working in hospital-based infectious disease clinics, many of whom had to be transferred to newly created, dedicated COVID-19 units. 8 Italy was the first European country to be hard hit by COVID-19, and the first to face the consequent severe hospital crisis. [9][10][11] The aim of this study was to evaluate the impact of COVID-19 on HIV suppression and the continuum of care among the PLWH attending a large HIV clinic in Milan, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced HIV care since the pandemic among FSW living with HIV in the DR is similar to other reports among PLHIV in other countries. 7,8,26 This study found that mental health challenges were the most robust predictor of the reduced HIV care since the pandemic. Other studies reported increased stress, anxiety, and depression among PLHIV in relation to the pandemic.…”
Section: Discussionmentioning
confidence: 69%
“…Reduced HIV care since the pandemic among FSW living with HIV in the DR is similar to other reports among PLHIV in other countries. 7,8,26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation